2022
DOI: 10.1037/emo0001059
|View full text |Cite
|
Sign up to set email alerts
|

Induced negative arousal modulates the speed of visual working memory consolidation.

Abstract: This study examines how induced negative arousal influences the consolidation of fragile sensory inputs into durable working memory (WM) representations. Participants performed a visual WM change detection task with different amounts of encoding time manipulated by random pattern masks inserted at different levels of memory-and-mask Stimulus-Onset-Asynchrony (SOA). Prior to the WM task, negative or neutral emotion was induced using audio clips from the International Affective Digital Sounds (IADS). Pupillometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 134 publications
(256 reference statements)
0
20
0
1
Order By: Relevance
“…As a result, tasks that capture control-related WM functions (e.g., the n-back task) often show reduced performance under negative emotion (e.g., Choi et al, 2013; Schoofs et al, 2008; Shackman et al, 2006). On the other hand, negative emotion could also increase the efficiency of information processing (Eysenck et al, 2007; Xie et al, 2022), such that memory items retained under the focus of attention in WM may be encoded with greater precision. Alternatively, this trade-off between the total amount of information retained in WM and the quality of remembered content could also be a result of a change in task strategy or information processing style induced by a negative emotional state (Storbeck, 2013; Storbeck & Clore, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, tasks that capture control-related WM functions (e.g., the n-back task) often show reduced performance under negative emotion (e.g., Choi et al, 2013; Schoofs et al, 2008; Shackman et al, 2006). On the other hand, negative emotion could also increase the efficiency of information processing (Eysenck et al, 2007; Xie et al, 2022), such that memory items retained under the focus of attention in WM may be encoded with greater precision. Alternatively, this trade-off between the total amount of information retained in WM and the quality of remembered content could also be a result of a change in task strategy or information processing style induced by a negative emotional state (Storbeck, 2013; Storbeck & Clore, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the current study has revealed a potential moderator of the experimental effect of induced negative emotion on WM. Although the induction and assessment of emotional experiences have been extensively investigated in the past several decades (e.g., Bradley & Lang, 1994; Miers et al, 2011; Schubert, 2011; Siedlecka & Denson, 2019; Vuoskoski & Eerola, 2011), emotional experiences induced using laboratory stimuli and procedures can vary significantly due to individual differences in various factors such as emotion sensitivity and resilience (Chen et al, 2018; Quigley et al, 2014; Xie, Cappiello, et al, 2018; Xie et al, 2022). Besides implementing more effective emotion induction procedures (Quigley et al, 2014), another essential step is to assess how the strength or intensity of induced emotional experiences across participants could modulate our experimental observations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations